The Visual dictionary of buildings. - Dorling Kindersley, Inc. (New York Dorling Kindersley, 1992)
Labeled illustrations with explanatory text depict historical and contemporary structures, architectural elements, and building components from ancient times to the present.
Keywords: Architecture -- Dictionaries; Decoration and ornament, Architectural -- Dictionaries; Architecture; Decoration and ornament, Architectural; Buildings